Epigenetic Properties of Compounds Contained in Functional Foods Against Cancer - Giulia Casari; Brenda Romaldi; Andrea Scirè; Cristina Minnelli; Daniela Marzioni; Gianna Ferretti; Tatiana Armeni (Biomolecules)
Epigenetics encompasses reversible and heritable genomic changes in histones, DNA expression, and non-coding RNAs that occur without modifying the nucleotide DNA sequence. These changes play a critical role in modulating cell function in both healthy and pathological conditions. Dysregulated epigenetic mechanisms are implicated in various diseases, including cardiovascular disorders, neurodegenerative diseases, obesity, and mainly cancer. Therefore, to develop innovative therapeutic strategies, research for compounds able to modulate the complex epigenetic landscape of cancer is rapidly surging. Dietary phytochemicals, mostly flavonoids but also tetraterpenoids, organosulfur compounds, and isothiocyanates, represent biologically active molecules found in vegetables, fruits, medicinal plants, and beverages. These natural organic compounds exhibit epigenetic modulatory properties by influencing the activity of epigenetics key enzymes, such as DNA methyltransferases, histone acetyltransferases and deacetylases, and histone methyltransferases and demethylases. Due to the reversibility of the modifications that they induce, their minimal adverse effects, and their potent epigenetic regulatory activity, dietary phytochemicals hold significant promise as antitumor agents and warrant further investigation. This review aims to consolidate current data on the diverse epigenetic effects of the six major flavonoid subclasses, as well as other natural compounds, in the context of cancer. The goal is to identify new therapeutic epigenetic targets for drug development, whether as stand-alone treatments or in combination with conventional antitumor approaches.